Neochromadora alejandroi sp. n. (Chromadorida: Chromadoridae) and Cobbia macrodentata sp. n. (Monhysterida: Xyalidae), two new species of free-living marine nematodes from the Patagonian coast - Lo Russo, Virginia (2012)
Two new species belonging to the genera Neochromadora and Cobbia from the coastal zone of Patagonia, in the Río Negro and Chubut provinces of Argentina, are described. Neochromadora alejandroi sp. n. is characterised by gubernaculum and spicule shape, the presence of a thick cuticle on subventral tail area, shape of the pharyngeal bulb and length of the cephalic and somatic setae. Cobbia macrodentata sp. n. is characterised by the amphid position, the presence of a large dorsal tooth, the size and length of the cephalic setae, the shape of the gubernaculum which has small hooks at the distal end and the presence of precloacal pores. Keys to the species of both genera are provided.